A review of the microwave-assisted synthesis of carbon nanomaterials, metal oxides/hydroxides and their composites for energy storage applications. Issue 27 (30th June 2021) - Devi, Nitika; Sahoo, Sumanta; Kumar, Rajesh; Singh, Rajesh Kumar
Abstract : Microwave-assisted synthesis of carbon nanomaterials, metal oxides/hydroxides and their composites for energy storage applications. Abstract : Currently, nanomaterials are considered to be the backbone of modern civilization. Especially in the energy sector, nanomaterials (mainly, carbon- and metal oxide/hydroxide-based nanomaterials) have contributed significantly. Among the various green approaches for the synthesis of these nanomaterials, the microwave-assisted approach has attracted significant research interest worldwide. In this context, it is noteworthy to mention that because of their enhanced surface area, high conducting nature, and excellent electrical and electrochemical properties, carbon nanomaterials are being extensively utilized as efficient electrode materials for both supercapacitors and secondary batteries. In this review article, we briefly demonstrate the characteristics of microwave-synthesized nanomaterials for next-generation energy storage devices. Starting with the basics of microwave heating, herein, we illustrate the past and present status of microwave chemistry for energy-related applications, and finally present a brief outlook and concluding remarks. We hope that this review article will positively convey new insights for the microwave synthesis of nanomaterials for energy storage applications.